2011
DOI: 10.1002/ccd.23116
|View full text |Cite
|
Sign up to set email alerts
|

Occupational radiation dose during transcatheter aortic valve implantation

Abstract: This study provides hitherto unavailable data on the radiation exposure of staff during transfemoral and transapical TAVIs. Relatively high doses were observed in the transapical approach. The dose of the right hand of the cardiothoracic surgeon will reach the annual limit within about 250 procedures per year, implying that hand dose measurements should become standard and that the number of procedures performed by the cardiothoracic surgeon involving X-rays may have to be limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…13,15,2426 Operator exposure (particularly hands) is of greater concern for the TA procedure relative to the TF approach. 26 One option to reduce radiation would be to perform valve deployment under fluoroscopy and store the sequence. Also, more significant utilisation of adjunctive modalities such as TEE for positioning of the valve has been shown to reduce contrast volume.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,2426 Operator exposure (particularly hands) is of greater concern for the TA procedure relative to the TF approach. 26 One option to reduce radiation would be to perform valve deployment under fluoroscopy and store the sequence. Also, more significant utilisation of adjunctive modalities such as TEE for positioning of the valve has been shown to reduce contrast volume.…”
Section: Discussionmentioning
confidence: 99%
“…The single dose per procedure of the operator is on the order of magnitude of one thousandth of the exposure of the patient [13] (Figure 1a). Effective occupational doses per procedure range from 0.02 to 38 microSv for diagnostic catheterization, 0.2 to 31.2 microSv for percutaneous coronary intervention, 0.2–9.6 microSv for ablation, 0.3–17.4 microSv for pacemaker or intracardiac defibrillation implantations [14] and may reach even higher values per procedure up to 50 microSv for dilation of chronic total occlusion and up to 100 microSv transcutaneous aortic valve [15] and up to 200 microSv per single procedure of endovascular thoraco-abdominal aneurysm repair [16]. The measurement over personal protective devices ranged from 0.4–1,100 microSv at the eye level, 1.2–580 microSv at the thyroid level, 32–750 microSv at the trunk level, and 0.4–790 microSv at head level, whereas measurements under the apron at the trunk levels ranged from 0 to 23 microSv [14].…”
Section: Reviewmentioning
confidence: 99%
“…The reviewers determined that the operator's fingers frequently receive the highest amount of radiation of all body areas 6 . Three other descriptive studies by Sauren et al, 4 Ginjaume et al, 7 and Häusler et al 8 also found that an operator's fingers receive larger doses of radiation than other areas of the body.…”
Section: Wearing Ring Dosimetersmentioning
confidence: 97%
“…Without the use of a ring dosimeter, hand and finger radiation exposure cannot be accurately recorded. This exposure level is important in determining the maximum allowable radiation dose recommended by the Occupational Safety and Health Administration (OSHA) for health care workers 4,5 . A ring dosimeter is intended to measure only the amount of radiation received by the fingers of the individual wearing it; therefore, it should be worn in addition to, and not in place of, other required dosimeters.…”
Section: Wearing Ring Dosimetersmentioning
confidence: 99%